1996
DOI: 10.1021/bi9609679
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Antiparallel DNA Triple Helix Formation

Abstract: We have used DNase I footprinting to examine the formation of antiparallel DNA triple helices on DNA fragments containing the homopurine target sites (GGA)2GGX(GGA)2GG.(CCT)2CCZ(CCT)2CC (where X.Z is each base pair in turn), with the GA- and GT-rich oligonucleotides, (GGA)2GGN(GGA)2GG and (GGT)2GGN(GGT)2GG (N = each base in turn). These were designed to form G.GC and A.AT or T.AT triplets with a central N.XZ mismatch, which should bind in an antiparallel orientation. We find that almost all combinations genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 32 publications
4
29
0
Order By: Relevance
“…Similarly in a REPSA selection assay for oligonucleotides which generate stable triplexes at a 19-mer target site, perfect matches were observed for the 13 bases at the 3'-end, while mismatches were selected at the 5'-end, and shorter oligonucleotides generated complexes with much reduced stability [179]. The greater effect of the 3'-end of the third strand has also been observed in footprinting experiments with oligonucleotides containing (GGA) n repeats, for which slipped structures were observed [171]. More recently this effect has been confirmed by Arimondo et al [180] who compared the strength of triplex formation by (AGG) 4 and (GGA) 4 4 ].…”
Section: Antiparallel Triplexes Lengthmentioning
confidence: 77%
See 2 more Smart Citations
“…Similarly in a REPSA selection assay for oligonucleotides which generate stable triplexes at a 19-mer target site, perfect matches were observed for the 13 bases at the 3'-end, while mismatches were selected at the 5'-end, and shorter oligonucleotides generated complexes with much reduced stability [179]. The greater effect of the 3'-end of the third strand has also been observed in footprinting experiments with oligonucleotides containing (GGA) n repeats, for which slipped structures were observed [171]. More recently this effect has been confirmed by Arimondo et al [180] who compared the strength of triplex formation by (AGG) 4 and (GGA) 4 4 ].…”
Section: Antiparallel Triplexes Lengthmentioning
confidence: 77%
“…In some studies antiparallel triplexes are shown to have very high affinities; short oligonucleotides exhibit nanomolar binding constants [169,170], while in other studies longer oligonucleotides, under similar conditions, fail to show binding at micromolar concentrations [137,[170][171][172][173].…”
Section: Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…60 This is in addition to the GA and GT TFOs themselves exhibiting different binding affinities to the target DNA duplex. 61 Most interestingly, the possibility of inducing a bend in a purine-rich tract of DNA duplex using a TFO is perceived when a G * GC triplet mediates between mini A * AT triplexes and vice versa (Figures 9-12). Twist angle and conformational variations in the RH strand together with an increase in WH groove width and variations in X-displacement of the WC duplex pairs at the nonisomorphic junctions are found to be the cause for bending.…”
Section: Discussionmentioning
confidence: 99%
“…Triple helical structures can also be obtained with a third strand containing pyrimidines and purines (GT-rich oligonucleotides) through formation of G•G.C and T•A.T base triples. Most reports concerning such GT third strand triple helices also considered an antiparallel third strand orientation (11)(12)(13)(14)(15)(16). It has been proposed that the number of GpT/TpG steps in the third strand will determine the orientation of the third strand with respect to the purine duplex strand.…”
Section: Introductionmentioning
confidence: 99%